Atypical viewing position effect in developmental dyslexia: A behavioural and modelling investigation. Issue 5 (4th July 2021) - Valdois, Sylviane; Phénix, Thierry; Fort, Mathilde; Diard, Julien
ABSTRACT: The probability of recognizing a word depends on the position of fixation during processing. In typical readers, the resulting word-recognition curves are asymmetrical, showing a left-of-centre optimal viewing position (OVP). First, we report behavioural results from dyslexic participants who show atypical word-recognition curves characterized by the OVP being right of centre with recognition probability being higher on the rightmost than on the leftmost letters. Second, we used BRAID, a Bayesian model of word recognition that implements gaze position, an acuity gradient, lateral interference and a visual attention component, to examine how variations in the deployment of visual attention would affect the OVP curves. We show that the atypical dyslexic curves are well simulated assuming a narrow distribution of visual attention and a shifting of visual attention towards the left visual field. These behavioural and modelling findings are discussed in light of current theories of visual attention deficits in developmental dyslexia.